Students' mathematical communication skills by applying the round club type of cooperative learning model in terms of linguistic intelligence - Mulia, Dira Utami; Masykur, Ruhban; Widyastuti, Rany (Desimal: Jurnal Matematika, 2021)
The purpose of this research is to determine the effect of the Round Club Type of Cooperative Learning model on mathematical communication skills in terms of linguistic intelligence. This research is a type of Quasy Experimental Design research with a  factorial research design. The population in this research were all 7th grade students of SMP Karya Bhakti Panaragan Tulang Bawang Barat. The sampling technique used is the Cluster Random Sampling technique with The Operation of Algebraic Form material. The sample consisted of two classes, namely the experimental class and the control class. Techniques in data collection used were mathematical communication skills tests and student linguistic intelligence questionnaires. The analytical technique used in this research is a two-way analysis of variance with unequal cells. Based on theoretical studies and calculations, it can be concluded that: there is an effect on students who use the Round Club type of cooperative learning model on mathematical communication skills, there is an influence of linguistic intelligence on mathematical communication skills, and there is no interaction between the Round Club type of Cooperative learning model and linguistic intelligence on mathematical communication skills.